Assessment of the relationship between hypoglycaemia awareness and autonomic function following islet cell/pancreas transplantation. Issue 6 (16th June 2015) - Kamel, Jordan T.; Goodman, David J.; Howe, Kathy; Cook, Mark J.; Ward, Glenn M.; Roberts, Leslie J.
Abstract Background This study assesses the autonomic function of patients who have regained awareness of hypoglycaemia following islet cell or whole pancreas transplant. Methods Five patients with type 1 diabetes and either islet cell (four patients) or whole pancreas (one patient) transplant were assessed. These patients were age‐matched and gender‐matched to five patients with type 1 diabetes without transplant and preserved hypoglycaemia awareness and five healthy control participants without diabetes. All participants underwent (i) a battery of five cardiovascular autonomic function tests, (ii) quantitative sudomotor axonal reflex testing, and (iii) sympathetic skin response testing. Results Total recorded hypoglycaemia episodes per month fell from 76 pre‐transplant to 13 at 0‐ to 3‐month post‐transplant (83% reduction). The percentage of hypoglycaemia episodes that patients were unaware of decreased from 97 to 69% at 0–3 months (p < 0.001, Fisher's exact test) and to 20% after 12 months (p < 0.0001, Fisher's exact test). This amelioration was maintained at the time of testing (mean time: 4.1 years later, range: 2–6 years). Presence of significant autonomic neuropathy was seen in all five transplanted patients (at least 2/3 above modalities abnormal) but in only one of the patients with diabetes without transplantation. Conclusions The long‐term maintenance of hypoglycaemia awareness that returns after islet cell/pancreas transplantation in patients with diabetes is not prevented by significant autonomic neuropathy and is better accounted for by other factors such as reversal of hypoglycaemia‐associated autonomic failure. Copyright © 2015 John Wiley & Sons, Ltd.